2016
DOI: 10.1021/acs.jpclett.6b00475
|View full text |Cite
|
Sign up to set email alerts
|

Novel Excitonic Solar Cells in Phosphorene–TiO2 Heterostructures with Extraordinary Charge Separation Efficiency

Abstract: Constructing van der Waals heterostructures is an efficient approach to modulate the electronic structure, to advance the charge separation efficiency, and thus to optimize the optoelectronic property. Here, we theoretically investigated the phosphorene interfaced with TiO2(110) surface (1L-BP/TiO2) with a type-II band alignment, showing enhanced photoactivity. The 1L-BP/TiO2 excitonic solar cell (XSC) based on the 1L-BP/TiO2 exhibits large built-in potential and high power conversion efficiency (PCE), dozens … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 67 publications
0
43
0
Order By: Relevance
“…At the moment, research for its application in areas such as electronics, optoelectronics and batteries is in progress [4,5,6,8,50,51,52,53,54]. …”
Section: Device Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…At the moment, research for its application in areas such as electronics, optoelectronics and batteries is in progress [4,5,6,8,50,51,52,53,54]. …”
Section: Device Applicationsmentioning
confidence: 99%
“…On the other hand, its possibility as a water splitting photocatalyst has not been studied much. Recently, several researches adopted black phosphorus as a photocatalyst or photoelectrode [8,9,10]. Zhou et al [8] proposed TiO 2 , black phosphorus heterostructure for the solar cell and Sa et al [9] suggested strain engineering of the black phosphorus for its future application as a photocatalyst.…”
Section: Black Phosphorus As Water Splitting Photocatalystmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes the structures and properties of monolayer BP and bulk BP in comparison with the more mature and well‐studied graphene. On the basis of intrinsic characteristics, 2D BP has been investigated for use in various applications, including transistor,54, 60, 61, 62 solar cell,63, 64 thermoelectric,65, 66, 67 heterojunction p–n diode,68, 69 sensing,70, 71 photovoltaic devices,72 and photodetectors 73, 74…”
Section: Introductionmentioning
confidence: 99%